Standards and Global Trade : A Voice for Africa - Wilson, John S. (Washington, DC: World Bank, 2013)
The book provides information, and guidance for policymakers, the development community, and others in the critical area of "behind the border" barriers to trade. With a view to promoting efforts to strengthen Africa's capacity to meet trade standards, and comply with technical regulations, the book examines the link between those standards, and regulations and export success in case studies of five countries: Kenya, Mozambique, Nigeria, South Africa, and Uganda. Each chapter describe the economic context of trade standards in a country, and examines the mechanisms by which standards, and regulations are established, and revised at the local, and international levels. The authors - local experts in the region - review existing trade regulations, and determine the extent to which they are consistent with international practices. They also analyze each country's physical infrastructure, organizational capacities, and current standard implementation process, and, consider the probable impact of new standards, regulations, and related production/marketing practices in key industries. The first comprehensive assessment of the relationship between trade standards, and development priorities in Sub-Saharan Africa, this book offers concrete action plans for supporting African firms, and farmers in their efforts to improve product quality, and reach international markets in key commodity sectors.